Texts and Collations from the Deutsches Museum, München - Farber, Walter
copies Dt Mus. 36 733, Dt Mus. 36 734, Dt Mus. 1974/138, Dt Mus. 11 866b; ersch. 1981; various Sum. texts published in transcription by Sauren, OLP 8 (1977) 5-31.